Design and performance analysis of various high torque segmented rotor HE‐FSM topologies for aircraft applications. Issue 2 (16th January 2020) - Ali, Hassan; Sulaiman, Erwan; Kosaka, Takashi
Abstract : Electrical machines for aircraft applications require basic characteristics such as lightweight, high reliability, fault tolerance ability, and torque power and higher densities. Correspondingly, hybrid excitation flux switching machines (HE‐FSMs) are capable of producing significant characteristics of high torque and power by improving flux strengthening in the iron core. However, magnetic flux cancellation and leakage in HE‐FSMs cause the reduction of flux linkage created by permanent magnet (PM) and field excitation (FE), which leads to deterioration of electromagnetic torque. This study presents magnetic flux performance and comparison of various topologies of HE‐FSMs by employing different positions of PMs and FE coils on the stator core. The purpose of a segmented rotor is to deliver a well‐defined electromagnetic flux pathway for carrying magnetic flux to nearby armature coil on stator with rotor rotation to improve the flux strengthening. Moreover, magnetic performances of various proposed HE‐FSMs at different positions of PMs are investigated and compared based on 2D finite element analysis. Subsequently, the enhanced HE‐FSM III has successfully achieved flux strengthening of 22%, torque of 54% and power of 61% more than initial design of HE FSM I, respectively. In conclusion, the proposed HE‐FSM structures show the capability to match high torque and power for aircraft applications.